Control interno a la gestión del talento humano al personal administrativo basado en coso i en induhorst cía. Ltda., cantón quevedo, año 2023 - Sotomayor Sabando, Karina Liseth (2025)
This research aimed to evaluate the internal control system in the management of administrative human talent within an agro-industrial company located in Quevedo, during the year 2023, applying the COSO I framework. A mixed-methods, descriptive and evaluative approach was used, incorporating surveys to 24 administrative staff members, a semi-structured interview with the Financial Manager, and functional benchmarking with a peer company of similar size and sector. Findings revealed an overall compliance of 58% across the COSO I components: control environment (60%), risk assessment (45%), control activities (52%), information and communication (47%), and monitoring (42%). The survey indicated that 62% of employees view complaint and suggestion mechanisms as ineffective, 58% are unaware of their labor benefits, and 50% report irregular and subjective performance evaluations. Efficiency indicators showed 83.33% compliance in the selection process, an average of 25 days to fill vacancies, and 60% compliance in training plans. In terms of effectiveness, employee turnover was 10%, performance evaluations reached 70%, and employee satisfaction was 60%. Goal achievement by department stood at 83.33%, while internal communication was rated at a medium level. The study concludes that structural weaknesses in internal control hinder the efficiency, effectiveness, and overall performance of human talent management. A SMART-based improvement plan is recommended, focusing on digital process transformation, segmented training, implementation of performance indicators, and non-salary recognition strategies to strengthen organizational climate and retain key talent.